Caribbean stock exchange and the Internet. - JONES-HENDRICKSON, S.B. (1996)
Proposes a Caribbean Regional Stock Exchange which will begin to conduct business on the Internet. Argues that the Internet and the World Wide Web offer the equity markets of the Caribbean an opportunity to have wider informational flow, quicker decision-making, and greater transparency in stock trades, while the Internet lends itself to permitting greater access to a larger number of persons.